Clerodendranthus spicatus: a comprehensive review of the chemical constituents, pharmacology, quality control and clinical applications - Jiao, Xingmeng; Jin, Qiong; Zhu, Peifeng; Tan, Zhuomin; Li, Li; Liu, Lu (Frontiers in Pharmacology, 2025)
30 Clerodendranthus spicatus (CS), is an herbaceous perennial belonging to the family 31 Lamiaceae. The herb is extensively employed in traditional Chinese medicine for the 32 mitigation of nephritis, cystitis, kidney stones, urological tract stones, gout, and other 33 urinary conditions. Numerous research studies have been conducted in the past to 34 explore the traditional medicinal value, phytochemical composition, pharmacological 35 effects, and quality control measures associated with this plant. This has motivated us 36 to systematically search various online databases such as Google Scholar, PubMed, 37 Science Direct, Elsevier, CNKI, and Sci-Hub using specific keywords to get the most 38 recent research information findings related to this plant. Phytochemical investigations 39 have identified that this plant predominantly contains flavonoids, terpenoids, 40 phenylpropanoids, and volatile oil compounds. Certain constituents have been 41 employed as markers in quality assessment research, and some were recognized as 42 bioactive agents in the management of specific ailments. These components have 43 demonstrated notable effectiveness in combating bacterial infections, reducing 44 inflammation, providing antioxidant properties, managing hyperuricemia, and offering 45 renal protection. Notably, clinical trials have confirmed its remarkable efficacy in 46 treating urinary inflammation and stones. We acquired recent research findings 47 concerning CS in the fields of phytochemistry, pharmacology, quality control, and 48 clinical applications via online search. These findings have been summarized and 49 analysed to offer a valuable reference for further comprehensive research, development, 50 and utilization of CS.